The Impact of Secondary School Teachers’ Training Program on the Professional Development of In-Service Biology Teachers - SHAABAN, Eman; ABOU ALI, Imane (The Eurasia Proceedings of Educational and Social Sciences, 2018)
Teachers’ professional development is essential to achieve quality teaching, through gaining different classroom management techniques, different teaching strategies to cater for different students’ levels and needs, and an in-depth updated subject knowledge. In order to be a permanent teacher at the Lebanese secondary public schools, teachers must follow a specific training program at the Lebanese University, Faculty of Education. The aim of this research is to investigate the impact of the training program, given at the Lebanese university for in-service secondary biology teachers, on their professional development. The study employed descriptive quantitative methodology to answer the research question. A sample of 50 biology secondary teachers filled a questionnaire related to their perceptions about professional development at the beginning of the training and filled the same questionnaire after completing four courses: teaching biology I and II, practicum I and II. The data was analyzed using SPSS (Statistical Package for the Social Sciences). The results showed a significant relation between attending the training program and the teachers’ professional development, specifically in the axis related to their perceptions of themselves as science teachers. Based on this study continuous professional training for in-service teachers is highly recommended.